A life cycle assessment (LCA)-based approach to guiding an industry sector towards sustainability: the case of the Swedish apparel sector. (1st October 2016) - Roos, Sandra; Zamani, Bahareh; Sandin, Gustav; Peters, Greg M.; Svanström, Magdalena
Abstract: The environmental challenges associated with consumption of textiles have generally been investigated on product level in Life Cycle Assessment (LCA) studies. For social sustainability aspects, social hotspot analysis has instead been applied on the textile sector level. The aim with the industry sector approach developed by the authors was to enable assessment of different interventions in terms of how they contribute to reaching targets for environmental and social sustainability, on the sector level. The approach was tested in a case study on the Swedish apparel sector. The industry sector approach consists of three steps that address three different questions: 1) What is the current sustainability performance of the sector? 2) What is an acceptable sustainability performance for the sector? 3) Are proposed interventions enough to reach an acceptable sustainability performance? By answering these questions, it is possible to measure performance in relation to sector level targets and learn which types of interventions (technical improvements, behavioral changes, new business models, etc.), and which actors (manufacturers, retailers, consumers, authorities, etc.) that can potentially provide the greatest improvements. By applying the approach in the case study, conclusions could be drawn on whether specific interventions appear to be sufficient or not in relation to the set environmental targets. The influence of the interventions in relation to reaching targets for social sustainability was found to be the most difficult to measure due to lack of data. To spur the industry sector's stakeholders to actualize the full potential of the most effective environmental interventions, a scheme for structured evaluation of LCA results directed towards these prospective actors was developed. Based on the results from the study, actor-oriented advice could be provided. Highlights: LCA-based approach for guiding an industry sector towards sustainability. Planetary boundaries based targets for environmental and social sustainability. Actor-oriented evaluation to investigate the potential of interventions. The approach was tested in a case study on the Swedish apparel sector.